Cyber Mayday and the Day After: A Leader's Guide to Preparing, Managing, and Recovering from Inevitable Business Disruptions - Lohrmann (Wiley Data and Cybersecurity, 2022)
Monograph
fulltext
Keywords: Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing